2015
DOI: 10.1103/physrevb.91.064301
|View full text |Cite
|
Sign up to set email alerts
|

Neutron inelastic scattering measurements of low-energy phonons in the multiferroicBiFeO3

Abstract: We present neutron inelastic scattering measurements of the low-energy phonons in single crystal BiFeO3. The dispersions of the three acoustic phonon modes (LA along [100], TA1 along [010] and TA2 along [110]) and two low energy optic phonon modes (LO and TO1) have been mapped out between 300 K and 700 K. Elastic constants are extracted from the phonon measurements. The energy linewidths of both TA phonons at the zone boundary clearly broaden when the system is warmed toward the magnetic ordering temperature T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…An anomaly in the Bi-dominated modes around T N was interpreted as strong evidence for spin-phonon coupling. A more recent inelastic study performed between 300 and 700 K revealed no significant changes in the dynamic response with temperature [12], although broadening of the energy linewidths on heating towards T N was observed as in Ref. [11], leading to the suggestion that the low-energy lattice dynamics and magnetic order are coupled [11,12].…”
Section: Introductionmentioning
confidence: 80%
“…An anomaly in the Bi-dominated modes around T N was interpreted as strong evidence for spin-phonon coupling. A more recent inelastic study performed between 300 and 700 K revealed no significant changes in the dynamic response with temperature [12], although broadening of the energy linewidths on heating towards T N was observed as in Ref. [11], leading to the suggestion that the low-energy lattice dynamics and magnetic order are coupled [11,12].…”
Section: Introductionmentioning
confidence: 80%
“…1d ) is not commonly observed, and we identify it as a hybridized magnon–phonon mode (or magnon-polarons) in the BFO/LSMO heterostructure, which propagates with a high group velocity and long decay length of up to 1 mm. The group velocity of 2.5 km s −1 observed by TR-BLS suggests that it associates with the BFO phonon mode 24 , 32 . The assumed hybridization of a phonon mode in BFO with magnons in LSMO and its angular dependency are substantiated by a theoretical approach considering the magnon–phonon coupling 33 – 36 at the BFO/LSMO interface which possesses both ferromagnetism and magnetoelastic coupling simultaneously (Fig.…”
Section: Introductionmentioning
confidence: 91%
“…The samples were therefore tilted 49 • from normal to reduce helium implantation in the bottom electrode and the substrate while also avoiding channeling through the crystal structure's easy planes. The TRIM simulations of the implanted ion distribution and depth profile-taking density values of 8.408 g cm −3 for BiFeO 3 , 6.49 g cm −3 for SrRuO 3 , and of 5.11 g cm −3 for SrTiO 3 as taken from the literature [42,43]-are shown in Figs. 1(d) and 1(e).…”
Section: Methodsmentioning
confidence: 99%